Modernisasi Manajemen Pendidikan Dayah Perspektif Al-Qur'an - Rahmad, Saiful; Sarnoto, Ahmad Zain; Arief, Armai (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This article examines the modernization of education management in Dayah from the perspective of the Al-Qur’an, highlighting key concepts such as Tajdîd (renewal), Taghyîr (change), Tabdîl (replacement), and Ishlȃh (improvement). This research employs a qualitative approach through literature review and documentation to explore how the values of the Al-Qur’an can serve as a foundation for the renewal of the Dayah education system. Tajdîd is reflected in the integration of the general curriculum and the strengthening of religious material as a response to the demands of the times. Taghyîr is seen in the changes to the management structure as well as in the use of technology in the teaching and learning process. Meanwhile, Tabdîl is manifested through the replacement of traditional teaching methods with a more interactive and contextual approach. Ishlȃh is represented by the adjustment of Dayah education regulations based on Law No. 18 of 2019, which harmonizes traditional values with modern needs. The findings of this study indicate that the process of modernizing Dayah education does not have to relinquish its spiritual identity, but can be carried out holistically by integrating modern managerial principles and Qur’anic values. This approach offers a more balanced transformative alternative between the scholarly, managerial, and spiritual aspects in building an adaptive and sustainable Islamic education system.